2019
DOI: 10.4174/astr.2019.97.3.130
|View full text |Cite
|
Sign up to set email alerts
|

One hundred sixty pancreaticoduodenectomies for periampullary cancers in a growing-volume setting: a single-institution and a single-surgeon's experience

Abstract: Purpose Many studies have concluded that cancer patients may have better outcomes when their surgery is performed in high-volume centers, especially when the procedure is pancreaticoduodenectomy (PD). However, some studies concluded that experienced surgeons or incorporation of expertise from high-volume centers may achieve satisfactory outcomes after PD in low-volume centers. Methods I retrospectively collected and analyzed the outcomes of PD for periampullary cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…While the literature is replete with multi-institutional and national/regional studies comparing outcomes after PD according to annual hospital volumes, very few have attempted to identify similarities and/or differences when assessing a single institution throughout the years of its maturation. 17-19 A study from India retrospectively evaluated 200 patients who underwent PD between 2002 and 2013 and found significantly decreased morbidity, LOS, and mortality for the high-volume period, which was defined as >25 PD/year. 17 Another single-institution study from Sweden evaluated 221 patients who underwent PD from 2000 to 2012 and found significantly decreased reoperation rate and LOS in the high-volume period, which was defined as ≥25 PD/year; however, the decrease in mortality did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…While the literature is replete with multi-institutional and national/regional studies comparing outcomes after PD according to annual hospital volumes, very few have attempted to identify similarities and/or differences when assessing a single institution throughout the years of its maturation. 17-19 A study from India retrospectively evaluated 200 patients who underwent PD between 2002 and 2013 and found significantly decreased morbidity, LOS, and mortality for the high-volume period, which was defined as >25 PD/year. 17 Another single-institution study from Sweden evaluated 221 patients who underwent PD from 2000 to 2012 and found significantly decreased reoperation rate and LOS in the high-volume period, which was defined as ≥25 PD/year; however, the decrease in mortality did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%